Apakah profitabiltas, risiko keuangan dan ukuran perusahaan meningkatkan praktik perataan laba perusahaan? - Erliana Banjarnahor; Khirstina Curry (STIE Perbanas Surabaya, 2017)
Earnings Management is the selection accounting policies by management to achieve certain goals. The usual way of management to influence the numbers on the financial statements is to make earnings management one of them with income smoothing. The purpose of this research is to test empirically the influence of profitability, financial risk, and company size to the practice of income smoothing. Population in this research is all public company year 2012-2016, while for sample of research use purposive sampling method, with secondary data. Methods of data analysis using binary logistic regression. The result obtained is profitability does not affect the income smoothing action. Financial risk does not affect earnings smoothing. Firm size affects earnings smoothing action. Positive influence means that if the size of the company the higher the company doing income smoothing.